RELEVANSI PENDIDIKAN KARAKTER KI HAJAR DEWANTARA DENGAN PAUD DI INDONESIA - Rizkina, Van Biaila; Kuswanto, Kuswanto (UNIVERSITAS SLAMET RIYADI, 2020)
This research aims to determine the relationship between the character education theory of Ki Hajar Dewantara on early childhood education in Indonesia. This research uses qualitative research methods by comparing several sources related to the title of this article. The approach uses analytical descriptive based literary studies. Ki Hajar Dewantara is one of the Indonesian education figures who make character education as a concept in education. Early childhood education was the earliest stage of the birth and growing characteristics of a child. Ki Hajar Dewantara implements character education in early childhood education by carrying the concept of